Psammobatis bergi, Blotched Sandskate - Pollom, R. (2020)
The Blotched Sandskate (Psammobatis bergi) is a small (to 61 cm total length) skate that occurs in the Southwest Atlantic from Rio de Janeiro, Brazil to the northern San Jorge Gulf, Chubut, Argentina. It inhabits the inner continental shelf at depths of 10-80 m. It is caught in demersal trawl fisheries, which are intense in parts of its range. It is typically discarded dead where caught. Its continued common presence in trawls and its small size suggest that it may have a productive enough life history to withstand fishing pressure and the population is suspected to be stable. Therefore, the Blotched Sandskate is assessed as Least Concern.